The Potential of Integrated Reporting to Enhance Social and Environmental (Sustainability) in Universities - Yuliarti, Enny; Sundari, Sri; Madein, Afdal (Universitas Negeri Padang, 2024)
Purpose – This research aims to examine the potential application of International Relations (IR) in annual reports that can influence social and environmental disclosure (sustainability) through a case study approach at the University of Indonesia, using the longitudinal content analysis method.Design/methodology/approach – The study analyzes the UI IR annual reports from 2015 to 2022 using three analytical tools: the annual report analysis framework, sustainability reporting framework, and IIRC framework.Findings – The findings indicate that the UI annual reports have fulfilled the indicators of GRI G3 and G4, campus sustainability assessment tools, and elements of the IIRC framework. This research also employs stakeholder theory and legitimacy theory to understand the importance of implementing sustainability practices at UI and how it relates to the university's relationships with its stakeholders.Originality/value – The findings of this research contribute to the literature in the fields of sustainability and International Relations (IR) in the public sector, particularly in universities. It provides insights into the potential of IR that influences social and environmental disclosure (sustainability) within universities and the possibilities for widespread application.Research limitations/implications – The limitation of this study is that only the UI annual reports were analyzed, so it is not precisely known to what extent sustainability practices are implemented in the university's operations. Further research can explore the factors influencing the adoption of sustainability practices by other universities in Indonesia and globally, as well as the challenges that may arise in the implementation process.